Improving learning & teaching quality in higher education - Scott, Geoff (South African Journal of Higher Education, 2016)
This paper argues that, to manage the powerful combination of change forces currently bearing down on higher education (HE) around the world successfully, universities have be good at determining not only what needs to change in their current approaches to learning and teaching (L&T) but also how to ensure that their agreed change priorities are consistently and effectively implemented and sustained. In doing this, the paper seeks to • bring together the lessons learnt from 40 years’ practical experience in improving L&T in universities and colleges with research on successful approaches to change implementation and leadership in HE; • show how these lessons have been successfully applied to improve the quality and performance of L&T in one university in a demonstrable manner; and • provide a framework for the effective management of L&T quality improvements in all our universities. The paper is based on a keynote address given at the South African Association for Institutional Research Forum in October 2011 and the discussions that followed.